Forgiveness Therapy: Improving Parents' Forgiving Ability in Adolescent Divorce Victims in Orphanages - Rina Rifayanti; Nadya Novia Rahman; Maulidatunnisa Maulidatunnisa; Afni Nurvita Damayanti Wijaya (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
This study aims to decide the effectiveness of the effect of forgiveness therapy to increase the ability of forgiveness in adolescent victims of divorce in orphanages. The research design used was a single group pretest posttest design. The research subjects were 25 adolescents in Ruhama Orphanages that all included into experimental group. Forgiveness ability is measured using the heartland forgiveness scale developed by Thompson et al. Data analysis used the Wilcoxon with the help of the Statistical Package for Social Science (SPSS) version 26.0 for windows. The results of the analysis used the Wilcoxon test which compared the forgiveness ability scores in the experimental group between before and after the treatment showed a value of Z = -0.514 and p = 0.607 (p more than 0.05) which means that there were no differences in forgiveness ability scores before and after being given the forgiveness therapy so there was no significant increasing forgiveness ability after being given the forgiveness therapy.Abstrak: Penelitian ini bertujuan untuk mengetahui efektivitas pengaruh forgiveness therapy untuk meningkatkan kemampuan pemaafan pada remaja di panti asuhan. Rancangan penelitian yang digunakan adalah single group pretest-posttest design. Subjek penelitian sebanyak 25 siswa remaja laki-laki di Panti Asuhan Ruhama yang seluruhnya tergabung pada kelompok eksperimen. Pemaafan diukur dengan skala Heartland Forgiveness Scale yang dikembangkan oleh Thompson dkk. (2005). Analisis data menggunakan Wilcoxon dengan bantuan program Statistical Package for Social Science (SPSS) versi 26.0 for windows. Hasil analisis menggunakan uji Wilcoxon yang membandingkan skor kemampuan pemaafan pada kelompok eksperimen antara sebelum dan sesudah perlakuan menunjukkan nilai Z = -0.514 dan p = 0.607 (p lebih dari 0.05) yang artinya tidak terdapat perbedaan skor kemampuan pemaafan sebelum dan sesudah diberikan perlakuan forgiveness therapy sehingga tidak terdapat peningkatan kemampuan pemaafan yang signifikan setelah diberikan perlakuan forgiveness therapy.